Enhancing rural public primary school teachers' information and communication technology (ICT) knowledge through holiday skill development programme (2009)
The use of information and Communication Technology (ICT) within the four walls of classroom is posing challenges to praticing teachers. This study therefore, investigated the impact of skill development programme organised for rural public primary schools on their ICT knowledge acquisition. The impact of the level of educational qualification attained on ICT knowledge acquisition was also investigated. The study was an experimental study which adopted single group pretest postest research design. Six hundred and thirty six primary school teachers randomly selected from seven rural local government area (LGAs) in Nigeria were used. The instrument used for data collection was ICT Test ( KR20=0.7). The data generated was analysed using paired t-test , analysis of covariance and Scheffe post hoc test. It was found in the study that the skill development programme has significant main effect on rural primary school teachers' knowledege acquisition on ICT (p<0.05). The level of educational qualification was slso found to have significant effect on the ICT knowledge acquisiton of the teachers (p<0.05). The knowledge of ICT is needed to be enhanced in teachers becuase in a teacher can only make use of the skill he/ she possessess. ICT is known to promote effective teaching and also enhances the involvement of the study and withdrawn learners. It is therefore imperative to equip all the rural teachers with ICT skill through periodic skill development programmes. This will improve the lot of their pupils.